The Darker Side of Motivation: Demotivation and Its Relation with Two Variables of Anxiety among Iranian EFL Learners. (29th February 2012) - Rastegar, Mina; Akbarzadeh, Mahboubeh; Heidari, Nahid
Abstract : The present study is an attempt to explore any significant relationships between demotivation, test anxiety (TA), and foreign language classroom anxiety (FLCA) and to seek any significant differences between males and females regarding demotivation, TA, and FLCA. One hundred Iranian EFL students studying at the departments of foreign languages of Shahid Bahonar University of Kerman took part in this study. In order to obtain the required data, three questionnaires were utilized: the Demotivation questionnaire (Kikuchi and Sakai, 2007) to measure demotivation, the Test Anxiety Scale ((TAS), Sarason, 1975) to measure test anxiety, and the Foreign Language Classroom Anxiety Scale (FLCAS, Horwitz, Horwitz, and Cope, 1986) to determine the level of students' FLCA. The findings of this study revealed the following first, there was a significant positive relationship between demotivation and TA; second, there was a significant positive relationship between demotivation and FLCA; third, there was a significant positive relationship between TA and FLCA, finally, there were no significant differences between males and females regarding demotivation, TA, and FLCA.